Profile of Rapid Molecular Test of Tuberculosis Using Xpert MTB/RIF - Faigah Aprilia Sy Faraid; Irda Handayani; Tenri Esa (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
Tuberculosis (TB) ranked the 10th highest cause of death in the world in 2016 according to the World Health Organization (WHO). To date, TB remains a top priority and is one of the goals in Sustainability Development Goals (SDGs), suggesting an urgent need of rapid detection methods for proper diagnosis and treatment. Rapid molecular test using Xpert MTB/RIF is one of the detection methods for TB diagnosis and it is expected to be able to early detect TB cases and anti-tuberculosis drug resistance. The purpose of this study was to determine the profile of rapid molecular test of tuberculosis using Xpert MTB/RIF device in the period of September 2017-August 2018 at Dr. Wahidin Sudirohusodo Hospital, Makassar. This study was retrospective research with a cross-sectional method using secondary data of rapid molecular test of Xpert MTB/RIF in the period of September 2017-August 2018. Data were statistically analyzed using SPSS version 22 and Chi-Square test with a significance value of 0.05. From 527 sputum samples, 96.8% adult TB was predominantly found. The "MTB not detected", "MTB detected”, and "MTB detected with Rif resistance” result was predominantly found in the 74.6% TB non-HIV group; 42.4% TB-HIV group, and 3.8% Non-HIV TB group. There were remarkably higher number of "MTB not detected” results of rapid molecular tests using Xpert MTB/RIF device in the group of pediatric and adult TB. The proportion of "MTB not detected" was higher in the TB-Non-HIV group; while the "MTB detected, Rif-sensitive" was higher in the TB-HIV group and the "MTB detected, Rif-resistance" was higher in the TB-Non-HIV group. It was recommended to carry out further research by performing diagnostic tests consisting of Acid-Fast Bacilli, rapid molecular test with Xpert MTB/RIF, and MTB culture.